YB1 dephosphorylation attenuates atherosclerosis by promoting CCL2 mRNA decay - Tang, Yaqin; Li, Zhiwei; Yang, Hongqin; Yang, Yang; Geng, Chi; Liu, Bin; Zhang, Tiantian; Liu, Siyang; Xue, Yunfei; Zhang, Hongkai; Wang, Jing; Zhao, Hongmei (Frontiers in Cardiovascular Medicine, 2022)
Chronic inflammation is a key pathological process in atherosclerosis. RNA binding proteins (RBPs) have been reported to play an important role in atherosclerotic plaque formation, and they could regulate the expression of inflammatory factors by phosphorylation modification. Y box binding protein 1 (YB1) is an RBP that has participated in many inflammatory diseases. Here we found an increased expression of phosphorylated YB1 (pYB1) in atherosclerotic plaques and demonstrated that YB1 dephosphorylation reduced lipid accumulation and lesion area in the aorta in vivo. Additionally, we found inflammatory cytokines were downregulated in the presence of YB1 dephosphorylation, particularly CCL2 which participates in the pathogenesis of atherosclerosis. Furthermore, we demonstrated that CCL2 mRNA rapid degradation was mediated by the glucocorticoid receptor-mediated mRNA decay (GMD) process during YB1 dephosphorylation, which resulted in the downregulating of CCL2 expression. In conclusion, YB1 phosphorylation affects the development of atherosclerosis through modulating inflammation, and targeting YB1 phosphorylation could be a potential strategy for the treatment of atherosclerosis by anti-inflammation.